2021
DOI: 10.1097/corr.0000000000001817
|View full text |Cite
|
Sign up to set email alerts
|

Does the Use of Sanders Staging and Distal Radius and Ulna Classification Avoid Mismatches in Growth Assessment with Risser Staging Alone?

Abstract: Background Although Risser stages are visible on the same radiograph of the spine, Risser staging is criticized for its insensitivity in estimating the remaining growth potential and its weak correlation with curve progression in patients with adolescent idiopathic scoliosis. Risser staging is frequently accompanied by other skeletal maturity indices to increase its precision for assessing pubertal growth. However, it remains unknown whether there is any discrepancy between various maturity paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…There are multiple skeletal maturity measures currently in use for assessing growth, including Risser staging 11 , triradiate cartilage closure [12][13][14] , Sanders staging (SS) 15 , the distal radius and ulna (DRU) classification 16 , and the proximal humeral ossification system (PHOS) 17 . Unlike the poor sensitivity of Risser staging for predicting PHV 18,19 , SS and the DRU classification have been found to be effective for indicating peak growth 7,14,20 , predicting curve progression in adolescent idiopathic scoliosis (AIS) 21,22 , and deciding when to wean from brace wear 23 . Despite these advantages, assessment requires a hand and wrist radiograph, resulting in additional radiation exposure.…”
mentioning
confidence: 99%
“…There are multiple skeletal maturity measures currently in use for assessing growth, including Risser staging 11 , triradiate cartilage closure [12][13][14] , Sanders staging (SS) 15 , the distal radius and ulna (DRU) classification 16 , and the proximal humeral ossification system (PHOS) 17 . Unlike the poor sensitivity of Risser staging for predicting PHV 18,19 , SS and the DRU classification have been found to be effective for indicating peak growth 7,14,20 , predicting curve progression in adolescent idiopathic scoliosis (AIS) 21,22 , and deciding when to wean from brace wear 23 . Despite these advantages, assessment requires a hand and wrist radiograph, resulting in additional radiation exposure.…”
mentioning
confidence: 99%
“…it is also prudent to note that the cobb angle at brace weaning is another risk factor of progression after maturity. [49][50][51][52] Patients with cobb angle reaching 40° is a well-established cutoff for adulthood progression. 4,53 similarly, those with this benchmark at the time of brace-weaning also have the potential for post-maturity progression.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were braced according to the Scoliosis Research Society (SRS) criteria (less than one year post-menarche; major curve magnitude between 25° and 40°; Risser stage ≤ 2; no previous treatment), 20 with two additional considerations. First, patients with Risser stage> 2 were braced if they had a radius grade ≤ 8 or ulna grade ≤ 7, 21 , 22 according to the distal radius and ulna classification (DRU). 23 This was because Risser staging offers limited information about the timing of the adolescent growth spurt compared to the DRU, 21 , 24 , 25 and patients with a radius grade of 8 and ulna grade of 7 still have significant potential for growth and curve progression.…”
Section: Methodsmentioning
confidence: 99%
“…First, patients with Risser stage> 2 were braced if they had a radius grade ≤ 8 or ulna grade ≤ 7, 21 , 22 according to the distal radius and ulna classification (DRU). 23 This was because Risser staging offers limited information about the timing of the adolescent growth spurt compared to the DRU, 21 , 24 , 25 and patients with a radius grade of 8 and ulna grade of 7 still have significant potential for growth and curve progression. 21 , 22 Second, patients with curve ≥ 35° were braced if they had a radius grade ≤ 9 or ulna grade ≤ 8, regardless of Risser staging, as it has been shown that these patients have high and moderate risks of progression to 40° and 50°, respectively.…”
Section: Methodsmentioning
confidence: 99%